The Ability of 1st Class Students of SMAN 11 Enrekang to Arrange Verbal and Nominal Sentences - Hasnia Hasnia; Citra Andini; M Dalyan Tahir; Hunaeni Hunaeni; Zulfikariandi Zulfikariandi; Muslimin MT (Hasanuddin University, 2022)
This research aims to reveal the ability of 1st graders of SMAN 11 Enrekang in compiling verbal and nominal sentences using the simple present tense and the difficulties that occur when compiling verbal and nominal sentences using the simple present tense. The researcher used quantitative method by applying the Surface Strategy Taxonomy in analyzing the data. The results of this research indicating that there are four types of errors. The frequency and percentage based on the surface strategy taxonomy are 63.59% misformation, then 16.18% addition, 13.88% omission, and 6.35% misordering. Furthermore, there are three difficulties experienced by students in compiling verbal and nominal sentences using the simple present tense, 1) Students do not understand the grammatical system; 2) students just write down what comes to mind without following the grammar; and 3) students do not understand vocabulary. The teachers recommend practicing grammar rules, in the simple present tense for mistakes. In addition, other researchers can provide techniques to improve students' mastery of the simple present tense